Increased contribution of wheat nocturnal transpiration to daily water use under drought. Issue 3 (6th December 2017) - Claverie, Elodie; Meunier, Félicien; Javaux, Mathieu; Sadok, Walid
Abstract : Increasing evidence suggests that in crops, nocturnal water use could represent 30% of daytime water consumption, particularly in semi‐arid and arid areas. This raises the questions of whether nocturnal transpiration rates (TRN ) are (1) less influenced by drought than daytime TR (TRD ), (2) increased by higher nocturnal vapor pressure deficit (VPDN ), which prevails in such environments and (3) involved in crop drought tolerance. In this investigation, we addressed those questions by subjecting two wheat genotypes differing in drought tolerance to progressive soil drying under two long‐term VPDN regimes imposed under naturally fluctuating conditions. A first goal was to characterize the response curves of whole‐plant TRN and TRN /TRD ratios to progressive soil drying. A second goal was to examine the effect of VPDN increase on TRN response to soil drying and on 13 other developmental traits. The study revealed that under drought, TRN was not responsive to progressive soil drying and – intriguingly – that TRN seemingly increased with drought under high VPDN consistently for the drought‐sensitive genotype. Because TRD was concomitantly decreasing with progressive drought, this resulted in TRN representing up to 70% of TRD at the end of the drydown. In addition, under drought, VPDN increase was found not to influence traits such as leaf area or stomata density. Overall, those findings indicate that TRN contribution to daily water use under drought might be much higher than previously thought, that it is controlled by specific mechanisms and that decreasing TRN under drought might be a valuable trait for improving drought tolerance.